Analysis of Determinant Factors in Student Decision Making in Choosing a Study Program in a Pesantren-based College - Abdul Aziz Sebayang; Zuhair Mubarrak Hazaa; Ahmad Faisal; Irwan Haryono Sirait (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Pesantren-based universities present a unique educational environment where religious and cultural values strongly influence students’ academic choices. This study analyzes the factors influencing students' decision-making in selecting study programs within this context. Using a quantitative survey approach, data were collected through questionnaires from 22 prospective students of STIT Ar-Raudlatul Hasanah Medan for the 2024–2025 academic year. The Guttman scale measured responses across 18 decision factors, including parental direction, talent development, career, cost, peers, etc. The results show that talent development (mean = 0.91) and parental direction (mean = 0.86) were the most influential factors, followed by career considerations (mean = 0.81) and program reputation (mean = 0.73). Personal choice (0.77) and potential program advancement (0.77) also contributed significantly. In contrast, cost (0.41) and peer influence (0.55) were found to have a limited impact. The findings underscore the predominance of internal motivations and family influence over socioeconomic or peer-related variables. This study recommends that pesantren-based institutions tailor their curricula to align with students’ talents and career aspirations while fostering family involvement in academic decision-making. Future research should expand the sample size and include multiple pesantren-based institutions to ensure broader generalizability. Additionally, qualitative approaches could enrich understanding of the nuanced influence of pesantren culture on educational choices.